Maladaptive coping, victimization, and recidivism among Japanese adolescents and emerging adults. (May 2021) - Bui, Laura; Mori, Takemi; Furukawa, Akira; Tasaka, Akiko
Abstract: Background: Substance use and victimization are known to be related to juvenile recidivism. Self-harm, a factor that commonly accompanies substance use and victimization, is not known to be related to said recidivism but may be so in a welfare-oriented juvenile justice system as found in Japan. Objective: We examine the extent to which maladaptive coping, comprising substance use and self-harm, increases the rate of persistence in correctional institutions in light of other well-replicated factors of youth recidivism. The study, too, investigates the role of maladaptive coping in explaining the impact of victimization on correctional recidivism. Methods: We draw from a sample of 348 adolescents and emerging adults, between ages 12–19 years, who were initially detained at a Juvenile Classification Home and followed-up for an average of 3.35 years. Results: Findings indicate that maladaptive coping is significantly related to persistence in the system, although history of probationary supervision and gang membership also were significant explanatory factors. In addition, the direct effect of victimization was larger than the indirect effect of victimization through maladaptive coping. Conclusions: Unlike previous studies, self-harm is significantly related to recidivism. This suggests that recidivism reflects a need for help more so than for punishment. The wider implications are that juvenile justice systems characterized as punitive seem outdated in managing detained young people as they lack adequate prevention supports.